Penanggulangan Masalah Kesehatan dalam Kondisi Pasca Longsor di Desa Samaenre, Kecamatan Mallawa, Kabupaten Maros - Jumasni Adnan; Veronica Margareth Dampung (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
Abstract: Landslides that hit Indonesian territory caused various problems. Every landslide disaster will cause problems such as economic paralysis, environmental damage and also cause various diseases. Geographically, Samaenre village, Mallawa District, Maros Regency, South Sulawesi with high rainfall and an average temperature 32°C with rainy season approximately 8 months. Landslides often occur in Indonesia, especially in areas with steep slopes. Landslides and stagnant water also still have the potential to occur due to heavy rains. Samaenre area has the potential for landslides and waterlogging. The purpose of this activity is to increase public knowledge about the potential for landslides, problems that can arise after landslides and how to deal with post-landslide health problems. The community service activities were attended by 24 people and the counseling material could be delivered by all of the service teams so as to increase community knowledge about tackling health problems in post-landslide conditions.Keywords: Landslides, Samaenre village, health problems..